2021
DOI: 10.48188/so.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Forensic investigation of a mass grave at Ovčara, near Vukovar, of victims killed by the Serbian army in 1991

Abstract: Objective: To evaluate the contribution of forensic research to the discovery and analysis of mass graves of victims of the Yugoslav People’s Army and Serbian paramilitaries at Ovčara, near Vukovar, and to the identification of exhumed victims as missing persons who were forcibly removed from Vukovar Hospital on 20 November 1991. Methods: We analysed official international documentation and transcripts from the International Criminal Tribunal for the former Yugoslavia. Data on causes of death and injury clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…This data is similar to other third world countries and signifies the fact that most of these deaths may have occurred due to unplanned assault. 17,18 In contrast, Qazi et al (2019) found that blunt head and chest traumas accounted for the majority of fatalities (71.9%). 23 Finally, speaking of the most important aspect of this study we observed that more than half of the bodies exhumed were partially decomposed over 40% were in advanced decomposed state.…”
Section: Discussionmentioning
confidence: 97%
“…This data is similar to other third world countries and signifies the fact that most of these deaths may have occurred due to unplanned assault. 17,18 In contrast, Qazi et al (2019) found that blunt head and chest traumas accounted for the majority of fatalities (71.9%). 23 Finally, speaking of the most important aspect of this study we observed that more than half of the bodies exhumed were partially decomposed over 40% were in advanced decomposed state.…”
Section: Discussionmentioning
confidence: 97%